Hypoallergenic derivatives of Fel d 1 obtained by rational reassembly for allergy vaccination and tolerance induction. Issue 6 (June 2014) - Curin, M.; Weber, M.; Thalhamer, T.; Swoboda, I.; Focke‐Tejkl, M.; Blatt, K.; Valent, P.; Marth, K.; Garmatiuk, T.; Grönlund, H.; Thalhamer, J.; Spitzauer, S.; et al.
Summary Background and objective The major cat allergen Fel d 1 represents one of the most important respiratory allergens. Aim of this study was to engineer recombinant Fel d 1 derivatives with reduced IgE reactivity and preserved T cell epitopes for vaccination and tolerance induction. Methods Seven recombinant mosaic proteins were generated by reassembly of non‐IgE‐reactive peptides of Fel d 1 which contained the sequence elements for induction of allergen‐specific blocking IgG antibodies and T cell epitopes. Mosaic proteins were expressed in Escherichia coli using codon‐optimized synthetic genes and compared with Fel d 1 regarding structural fold by circular dichroism, IgE‐binding capacity, activation of allergic patients' basophils and ability to induce allergen‐specific blocking IgG antibodies upon immunization. Results Although each of the mosaic proteins had lost the alpha‐helical fold typical for Fel d 1, a strong reduction in IgE reactivity as well as allergenic activity in basophil activation assays was only obtained for three constructs, two reassembled fragments (Fel d 1 MB, Fel d 1 MC) and a fusion of the latter two (Fel d 1 MF) in which the cysteines of Fel d 1 MC were replaced by serines. Immunization of rabbits with Fel d 1 MB, MC and MF induced high levels of IgG antibodies that inhibited IgE reactivity of cat‐allergic patients to Fel d 1 in a comparable manner as IgG induced with the wild‐type allergen. Conclusions We report the development of hypoallergenic reassembled Fel d 1 proteins suitable for vaccination and tolerance induction in cat‐allergic patients.